Highly targeted stabilization and release behavior of hazardous substances in phosphogypsum. (November 2022) - Wu, Fenghui; He, Minjie; Qu, Guangfei; Zhang, Ting; Ren, Yuanchuan; Kuang, Linrui; Ning, Ping; Li, Junyan; Liu, Ye
Highlights: Solid state reaction was used for solidification and stabilization of phosphogypsum for the first time. The two-stage solidification/stabilization method of phosphogypsum was adopted. This study achieved the effect of long-term solidification and stabilization of phosphogypsum. Abstract: In this paper, an innovative method for highly targeted solidification/stabilization (S/S) of harmful substances in phosphogypsum (PG) was proposed. The release behavior of hazardous substances in PG after mixed reaction was explored using lime or carbide slag (CS) as alkaline regulator and then polyaluminium chloride (PAC), polyferric sulfate (PFS) and polyacrylamide (PAM) as highly targeted S/S agents. The experimental results show that lime has a long-term buffering effect on the pH of PG and a significant stabilizing effect on P, F and heavy metals. When more than 5 % lime was added, the leaching concentration of heavy metals was less than 0.1 mg/L. Moreover, PAM, PAC and PFS have remarkable S/S effects on P, F and heavy metals in the order of PAM > PFS > PAC. When the dosage of PAM was more than 5 %, the leaching concentration of P and F was less than 0.2 mg/L and 1 mg/L, respectively, and that of heavy metals tends to be 0 mg/L, indicating that PAM demonstrates a significant continuous S/S effect and thus provides a feasible pretreatment method for harmless filling, soil utilization and high value-added resource utilization of PG. The high targeted S/S technology of hazardous substances studied in this paper directly provides theoretical and data support for the harmless and resource-based treatment of large-scale solid waste PG produced, alleviates the pressure of solid waste environmental protection in the phosphorus chemical industry, and provides a new research idea for the harmless treatment of other toxic and harmful large-scale solid wastes, reducing the cost of solid waste treatment and simplifying the treatment process.